Larval Fish Assemblages in Coastal Waters of Bangladesh: Spatial and Seasonal Dynamics - Sk. Ahmad Al Nahid; Saifuddin Rana; Nargis Sultana; Jannatul Mawa; Sazeed Mehrab Souhardya; Ilias Ebne Kabir; Shahida Arfine Shimul; Md Masum Billah; Md Khurshid Alam Bhuiyan; Afsana Kabir Dipty; Sk Istiaque Ahmed; Md Jalilur Rahman; et al. (Conservation, 2024)
The distribution of fish larvae in estuaries is crucial for comprehending the functioning of these ecosystems and their role as nursery grounds for marine fish species. Data regarding larval fish assemblages in the coastal waters of Bangladesh are currently scarce. This study examines the spatial and seasonal dynamics of larval fish communities in these waters using a two-year sampling effort with a bongo net. This study investigates the diversity, abundance, and distribution of larval fishes at four sites (Bakkhali River Estuary, Moheshkhalipara, Naf River Estuary, and Rezu Khal Estuary) on the southeastern coast of Bangladesh. A total of 10,387 fish larvae representing 25 families were identified. Clupeidae (42.9%), Engraulidae (35.5%), Ambassidae (10.1%), Myctophidae (2.1%), and Gobiidae (1.9%) were the five most dominant families based on the larval catch composition. Marked seasonal differences in the larval fish abundance were observed. However, these differences were not observed when comparing the four sampled sites. Additionally, the correlation between environmental variables and the larval abundance indicated that salinity negatively influences (p < 0.001) the larval fish abundance. This is the first comprehensive investigation of larval fish assemblages in the coastal waters of Bangladesh. The findings of this study enhance our understanding of the nursery habitat requirements for the early development stages of both migratory and resident species in subtropical coastal waters, providing valuable information for potential applications in management and conservation efforts.